Evaluation of pregnancy outcomes in mothers with COVID-19 infection: a systematic review and meta-analysis - Masoumeh Simbar; Sima Nazarpour; Ali Sheidaei (Taylor & Francis Group, 2023)
Pregnant women are one of the endangered groups who need special attention in the COVID-19 epidemic. We conducted a systematic review and summarised the studies that reported adverse pregnancy outcomes in pregnant women with COVID-19 infection. A literature search was performed in PubMed and Scopus up to 1 September 2022, for retrieving original articles published in the English language assessing the association between COVID-19 infection and adverse pregnancy outcomes. Finally, in this review study, of 1790 articles obtained in the initial search, 141 eligible studies including 1,843,278 pregnant women were reviewed. We also performed a meta-analysis of a total of 74 cohort and case-control studies. In this meta-analysis, both fixed and random effect models were used. Publication bias was also assessed by Egger's test and the trim and fill method was conducted in case of a significant result, to adjust the bias. The result of the meta-analysis showed that the pooled prevalence of preterm delivery, maternal mortality, NICU admission and neonatal death in the group with COVID-19 infection was significantly more than those without COVID-19 infection (p<.01). A meta-regression was conducted using the income level of countries. COVID-19 infection during pregnancy may cause adverse pregnancy outcomes including of preterm delivery, maternal mortality, NICU admission and neonatal death. Pregnancy loss and SARS-CoV2 positive neonates in Lower middle income are higher than in High income. Vertical transmission from mother to foetus may occur, but its immediate and long-term effects on the newborn are unclear.